PENGERINGAN ALAMI DAN BUATAN SEPULUH JENIS KAYU NUSA TENGGARA BARAT (Air drying and kiln drying properties of 10 wood species from Nusa Tenggara Barat) - Efrida Basri; Syarif Hidayat (Jurnal Penelitian Hasil Hutan, 1993)
This report presents result of a study on air drying properties and kiln drying schedule of ten  wood species from  Nusa   Tenggara Barat. the study  was   carried out   based On data from  quick drying test. The result shows that, the quality of almost all of the species dried using  air drying method are  inferior compared with that obtained from kiln drying. the ten wood species used   in the study can be grouped into four  drying schedules,  ringin, kabaukafa, sabaha and niu can be grouped into schedules  1 (easy to dry), katowi and kencari schedule 2, whereas red monggo and konca schedule 3, and mongo schedule  4 (difficult to dry).